Evaluation of new generation loop recorders placed during surgical ablation for atrial fibrillation. Issue 7 (17th June 2018) - DeBoard, Zachary; Doty, John R.
Abstract: Background: Current postsurgical atrial fibrillation (AF) ablation guidelines encourage serial rhythm evaluation; however, traditional Holter monitoring may be cumbersome for patients and yield limited data. An implantable loop recorder (LR) may provide increased data on the incidence of postablation arrhythmias. We sought to evaluate the use of a new generation LR implanted during surgical AF ablation. Methods: A retrospective analysis was performed on adult patients undergoing surgical AF ablation. All patients had subcutaneous placement of a LR. Data were collected on patient demographics, concomitant surgical procedures, complications, loop recorder extraction, and additional arrhythmia interventions. Results: Thirty‐one patients underwent surgical AF ablation with intraoperative placement of a LR during the study period. The median age was 71 and the majority had long‐standing persistent AF. Mitral and aortic valve pathology was the most common reason for concomitant operations. Four devices were explanted prior to the completion of follow‐up due to high AF burdens detected by the LR requiring catheter ablation or pacemaker placement. A 100% correlation between in‐clinic rhythm detected by the LR and electrocardiogram was observed. No infectious complications, device malfunctions, or deaths occurred. Conclusions: LRs placed intraoperatively during surgical ablation of AF are feasible and with nominal, if any, complications. More comprehensive rhythm analysis may aid with determination of operative success and the need for additional intervention or cessation of antiarrhythmic or anticoagulant medications.